The decline of the Roman Empire from the perspective of Augustine of Hippo (Circe de clásicos y modernos, 2018)
The purpose of this article is to delve into the ethical, cultural, theological and political fabric of the Agustinian view, taking into consideration the fact that The City of God is framed in terms of apologetics. In other words, we will analyze the Agustinian ethical and theological mark as it is motivated by the decline of Rome, its aim as apologetics being that of showing that such a collapse was not due to the abandonment of the Roman deities on behalf of the Christian god and that, conversely, according to the Agustinian vision, Christian virtues are the only ones that could have given Rome its splendor back.
Keywords: Agustine of Hippo; ethics; politics; theology; apologetics